FRI0392 Relationships between bone loss and dickkopf-1 (DKK-1) serum levels in patients with systemic sclerosis. (23rd January 2014) - Seriolo, B.; Brizzolara, R.; Soldano, S.; Casabella, A.; Paolino, S.; Botticella, G.; Meroni, M.; Molfetta, L.; Sulli, A.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) patients might present an increased risk of osteoporosis as a result of the chronic inflammatory state, immobilization, use of glucocorticoids and other causes. The Wnt/β-catenin pathway is an ancient and evolutionarily conserved signaling pathway that has recently been identified a key promoters of the osteoblastogenesis hence of the new bone formation in inflammatory conditions. Dickkopf-1 (DKK-1) is a natural inhibitor of Wnt signaling pathway that could be involved in promoting osteoclastogenesis through suppression of osteoprotegerin. 1 In this study, bone mineral density (BMD) and DKK-1 levels were evaluated in SSc patients in order to investigate possible associations between bone loss and Dkk-1 concentrations, according to their different nailfold videocapillaroscopic (NVC) patterns of microangiopathy ("Early", "Active", and "Late"). 2 Methods: Sixty-one postmenopausal patients (mean age 63±7 years) affected by SSc ("early" n=15; "active" n=14 and "late" pattern n=32) and 43 age-matched healthy controls (mean age 62±5 years) were studied. BMD (g/cm 2 ) of the lumbar spine (L1 -L4 ) and of the proximal femur was analyzed using dual-energy X-ray absorptiometry (DXA) scan (Lunar Prodigy). DKK-1 serum levels were measured by ELISA methods (DKK-1 Immunoassay R&D System). NVC patterns were analyzed according to the previous reported methods. 2 Statistical analysis was performed by non-parametric tests. Results: Out of 61 enrolled SSc patients, 44 (72%) presented bone loss; in particular 21 (34%) showed osteoporosis and 23 (28%) osteopenia. BMD was found significantly lower in SSc patients than in matched control group (lumbar spine: 0.990±0.192 g/cm 2 vs 1.039±0.18 g/cm 2 ; femoral neck 0.715±0.203 g/cm 2 vs 0.823±0.09 g/cm 2 ; ward 0.559±0.175 g/cm 2 vs 0.639±0.10 g/cm 2 ; trocanther 0.660±0.09 g/cm 2 vs 0.719±0.11 g/cm 2 ; total hip 0.809±0.125 g/cm 2 vs 0.903±0.11 g/cm 2, overall significance p<0.001). T and Z scores showed lower values in SSc patients compared to healthy controls (lumbar spine: T=-1.56±0.62 vs -0.72±1.19, p<0.001; Z=0.19±1.45 vs 0.65±1.06, p<0.05 and total hip: T=-2.01±1.07 vs -0.80±0.89, p<0.001; Z=-0.63±0.64 vs -0.01±0.75, p<0.03, respectively). DKK-1 levels were found significantly higher in SSc patients than in control group (2691±909 pg/mL vs 2164±662 pg/mL, p<0.007). Interestingly, decreased BMD at lumbar spine/hip and increased Dkk-1 levels were found in patients with "late" pattern vs "early"/"active" NVC patterns (lumbar spine 0.870±0.150 g/cm 2 vs 1.077±0.165 g/cm 2 ; total hip 0.660±0.246 g/cm 2 vs 0.783±0.113 g/cm 2, all p<0.05, and Dkk-1 levels 3265±666 pg/mL vs 2033±697 pg/mL p< 0.001, respectively). Conclusions: Increased DKK-1 serum concentrations together with decreased bone mass seem present in SSc patients compared to healthy controls. The association with the "late" NVC pattern of microvascular damage (advanced disease), may suggest that diffuse hypoxia/ischemia related to the diffuse microangiopathy might be a promoting factor for osteoclastogenesis and bone loss. References: Krishnan V et al. J Clin Invest 2006 Cutolo M et al. Clin Exp Rheumatol 2007 Disclosure of Interest : None Declared